Femvertising in Indonesia: Is it really empowering women? (a literature studies) - Amanda Putri Nahumury (Jurnal Desain, 2025)
The feminist movement has had a positive impact on various industries, including the media and advertising sectors. When feminist values are applied in advertising, it is referred to as femvertising, which aims to empower women. This study aimed to examine femvertising practices in Indonesia and determine whether they have truly empowered women. The research used a qualitative descriptive method, with literature study as the main research approach. The research data was collected from books, news, and previous studies, and analyzed using Miles and Huberman's analytical techniques. The findings of the study show that femvertising in Indonesia has implemented five key pillars, including the utilization of diverse female talent, messaging that promotes female empowerment, pushing gender-norm boundaries, downplaying sexuality, and portraying women authentically. Therefore, femvertising in Indonesia has successfully empowered women, though there are still areas for improvement, such as avoiding perpetuating unrealistic standards. The study is limited by the number of previous studies used as the main source of literature review. Further research is recommended to expand and add research sources to provide a more comprehensive view of femvertising practices.